2023 Year in review: Early breast cancer - Guilherme Nader-Marta; Ann H. Partridge (Breast, 2024)
The results of several studies aiming to tailor early breast cancer treatment to individual risk were released in 2023. Axillary lymph node dissections and radiotherapy may be safely omitted in carefully selected patients. Sustained benefit from adjuvant CDK4/6 inhibitors was observed in high-risk hormone receptor-positive disease and the addition of immunotherapy to neoadjuvant chemotherapy improved pathological response. Continued benefit from perioperative pembrolizumab was reported in patients with triple negative breast cancer, while atezolizumab did not improve the risk of recurrence either pre- or postoperatively. The chance of pregnancy was higher in younger patients attempting to conceive after breast cancer.